Status of global health fellowship training in the United States and Canada (Canadian Medical Education Journal, 2019)
Background: Increasing numbers of residency graduates desire global health (GH) fellowship training. However, the full extent of training options is not clear. Objective: To identify clinical GH fellowships in all specialties in the U.S. and Canada and to describe their demographics, innovative features, and challenges. Methods: The authors surveyed program directors or designees from GH fellowships with a web-based tool in 2017. Program directors reported demographics and program characteristics. Results: The authors identified 85 potential programs. Fifty-four programs (63.5%) responded confirming 50 fellowships. The number of U.S. GH fellowship programs increased by 89.7% since 2010. One-third of fellowships accepted graduates from more than one specialty. The most common single-specialty programs were Emergency Medicine or Family Medicine. Fellowship duration was most commonly 24 months. Median size was one fellow per year. Funding and lack of qualified applicants were significant challenges. Most programs were funded through fellow billing for patient care or other means of self-support.   Conclusions: The number of U.S. and Canadian GH fellowship programs has nearly doubled since 2010. Programs reported lack of funding and qualified applicants as their most significant challenges. Consensus amongst stakeholders regarding training requirements may improve outcomes for future fellows, their employers, and the patients they serve.